Developing and testing an interface pressure control system in 3d printed transtibial prosthetic socket / Murad Abdullah Khamis Subih - Murad Abdullah Khamis , Subih (2019)
An interface pressure within prosthetic sockets plays a major role in the fitting and comforting of the user. The continuous change of residual limb size cause poor attachment of the residual limb within prosthetic socket and high interface pressure with skin issues. Thus, the purpose of this study is to control an interface pressure within 3D printed transtibial prosthetic socket. Electronic system was designed to control the interface pressure inside 3D printed socket. The electronic system was attached into the pylon of the prosthetic device in a small box. This system could manage the pressure distribution in the 3D printed socket through the inflation and the deflation of air bladders. The 3D printed socket was built with tiny air bladders which were integrated with the liner. The inflation and deflation of the air bladders inside the 3D printed socket can be controlled using the pre-programmed keypad. The system has three air bladders connected to three separate subsystems (mini pumps and release valve). Universal Testing Machine was used to apply various static loadings into the prosthetic device. The pressure distribution in 3D printed socket was evaluated using F- socket transducers. Pressures reduced and increased in subregions of the artificial stump during the inflation of air bladders. This system minimized the interface pressures within 3D printed socket via inflation of air bladders. Pressures reduction inside the 3D printed socket were recorded at all sides. Posterior and medial sides have been recorded the maximum pressure reduction during inflation of posterior and medial air bladders respectively. The highest pressure reduction was 7.97% which recorded at medial distal and 7.86 % at posterior distal. A notable change in anterior pressure due to not have anterior air bladder. The final product of this project will eliminate the use of expensive silicone liners, relieve the peak pressures on the amputee's residual limb bony areas, and lastly manage the inner size of the socket in order to accommodate the continuous changes of the residual limb, especially for diabetic amputees